Semantic Change in IShowSpeed’s YouTube Streaming - Dino Kilibia; Agustinus Hary Setyawan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The rapid development of digital technology and social media platforms has transformed human communication, particularly in live streaming contexts. This study investigates semantic change in the language used by IShowSpeed, a prominent YouTube streamer known for his expressive and improvisational communication style. The research aims to identify types of semantic shifts and analyze the factors influencing these changes. Using qualitative descriptive methods, data were collected from IShowSpeed’s livestreams and viral clips from 2024–2025, followed by transcription, categorization, and contextual analysis. The findings indicate that his language exhibits various types of semantic change, including broadening, narrowing, amelioration, pejoration, metaphorical extension, metonymy, synecdoche, and euphemism. Factors contributing to these shifts include linguistic mechanisms, historical and cultural contexts, psychological motivations, and social dynamics within digital communities, particularly among Generation Z. These results enrich the understanding of modern semantics, digital pragmatics, and the social construction of meaning in online environments